Self-repairing prefabricated component crack repair material and preparation method thereof

By introducing polyurethane side chains and self-healing capsules into the modified epoxy resin, the problem of curing and shrinking of epoxy resin is solved, and the high mechanical strength and self-healing performance of crack repair materials are achieved, and the repair efficiency is improved.

CN119774938APending Publication Date: 2025-04-08JIESHOU BAOYE RUIXIANG CONSTR INDUSTRIALIZATION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411679326.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art, epoxy resin will undergo large deformation and shrinkage during the curing process, resulting in the debonding of the two sides of the repair material and the crack interface, limiting its application in crack repair material.

Method used

By connecting the polyurethane in the side chain of the modified epoxy resin, a tightly entangled three-dimensional network structure is constructed to improve toughness, and during the curing process, micro-expansion is generated by reacting isocyanate groups with water, which promotes the diffusion of the repair material into the crack. At the same time, self-healing capsules are used. When the cracks are generated again, the capsule ruptures and releases the capsule core, reacting with moisture or moisture in the cracks to achieve bonding and sealing.

Benefits of technology

It effectively avoids the curing and shrinking of epoxy resin, enhances the mechanical strength and interface bonding strength of crack repair materials, and gives good self-repairing performance, improving repair efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a self-repairing prefabricated component crack repair material, which belongs to the technical field of crack repair material preparation, and comprises the following raw materials in parts by weight: 9-13 parts of modified epoxy resin, 0.5-2 parts of curing agent, 8-10 parts of self-repairing capsules, 90-100 parts of Portland cement, 20-30 parts of fly ash, and 3-5 parts of diluent; the invention improves the curing shrinkage phenomenon of the epoxy resin by introducing the modified epoxy resin with micro-expansion performance, effectively avoids the secondary cracks of the crack repair material caused by curing shrinkage, and improves the bonding strength and mechanical properties of the crack repair material; at the same time, the introduction of the self-repairing capsule can release the capsule core in time when the crack is generated again, so as to bond and seal the crack, and endow the repair material with good self-repairing performance; at the same time, Portland cement and fly ash are used as aggregates, so as to strengthen the compactness of the repair material and further enhance the strength of the repair material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of crack repair material preparation, and in particular relates to a self-repairing prefabricated component crack repair material and a preparation method thereof. Background Art

[0002] Concrete structures such as buildings and roads will develop various cracks due to long-term influence of climate, geology, load and other factors, which will seriously affect the quality and durability of cement building structures. If not repaired in time, it will lead to safety accidents such as collapse, causing huge economic losses and casualties.

[0003] In the prior art, when preparing prefabricated component repair materials, epoxy resin is usually added as a polymer filler to improve the mechanical properties of the repair material. However, the epoxy resin will undergo large deformation and shrinkage during the curing process, resulting in debonding between the repair material and both sides of the crack interface, limiting the application of epoxy resin in crack repair materials. Therefore, how to improve the curing shrinkage performance of epoxy resin and give the crack repair material self-healing properties is a technical problem that needs to be solved at present. Summary of the invention

[0004] The purpose of the present invention is to provide a self-repairing prefabricated component crack repair material and a preparation method thereof, so as to solve the problems in the background technology.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A self-repairing prefabricated component crack repair material, comprising the following raw materials in parts by weight:

[0007] 9-13 parts of modified epoxy resin, 0.5-2 parts of curing agent, 8-10 parts of self-repairing capsules, 90-100 parts of Portland cement, 20-30 parts of fly ash, 3-5 parts of diluent;

[0008] Furthermore, the modified epoxy resin is prepared by the following steps:

[0009] A1. Add 2,4-toluene diisocyanate to the polyether diol, stir and mix, react for 1-2 hours under a nitrogen atmosphere at 60-80° C., cool, then add 1,4-butanediol and trimethylolpropane, continue to react for 2-4 hours at room temperature, and then obtain a prepolymer intermediate by rotary evaporation;

[0010] A2, add the prepolymer intermediate to the epoxy resin, stir and mix, add trimethylolpropane triglycidyl ether, stir and react for 1-2 hours under a nitrogen atmosphere at 110-120° C., and cool to obtain a modified epoxy resin;

[0011] Among them, polyether diol and 2,4-toluene diisocyanate are used as reaction raw materials, 1,4-butanediol is used as a chain extender, and polymerization is carried out under the action of trimethylolpropane, a cross-linking agent, to obtain a prepolymer intermediate with a highly active terminal polyurethane. The polyurethane has good bonding strength and can improve its adhesion to cement-based materials. Trimethylolpropane triglycidyl ether is used as an active diluent and a blending method is adopted to react with the hydroxyl group of the epoxy resin side chain to obtain a modified epoxy resin containing a polyester amino branched structure.

[0012] Furthermore, the usage ratio of the polyether diol, 2,4-toluene diisocyanate, 1,4-butanediol and trimethylolpropane is 16-18 mL: 8.9-9.6 mL: 8-13 mL: 12.7-13.4 g.

[0013] Furthermore, the volume ratio of the epoxy resin, the prepolymer intermediate and trimethylolpropane triglycidyl ether is 20-25:8-13:2-6.

[0014] Furthermore, the self-repairing capsule is prepared by the following steps:

[0015] The polyethylene wax is stirred and dissolved at 120°C, and then paraffin is added. After continuing to stir and dissolve, the temperature is kept constant, diphenylmethane diisocyanate is added, and stirring is carried out at a rotation speed of 700-800rpm for 2-3h, and then the temperature is reduced to 100-110°C, perfluorotributylamine is added, and stirring is continued for 20-30min, and then the temperature is quickly reduced to 15-20°C and ultrasonically oscillated for 30min, and then filtered, washed, and dried to obtain a self-healing capsule.

[0016] Furthermore, the dosage ratio of the polyethylene wax, paraffin, diphenylmethane diisocyanate, and perfluorotributylamine is 19-31g:21-28g:76-82mL:400mL; wherein, polyethylene wax and paraffin are both thermoplastic materials, have good sealing and chemical stability, and are prone to rupture when subjected to crack tip stress. At the same time, diphenylmethane diisocyanate has good fluidity and high activity of isocyanate groups, and can directly react with active hydrogen such as water. Therefore, the inert solvent perfluorotributylamine is used as a stabilizer and diluent, and a melt-dispersion condensation method is adopted to obtain a self-repairing capsule with polyethylene wax and paraffin as a composite capsule wall and toluene diisocyanate as a capsule core.

[0017] A method for preparing a self-repairing prefabricated component crack repair material comprises the following steps:

[0018] The modified epoxy resin, curing agent, self-repairing capsule, silicate cement, fly ash and diluent are placed in a stirring pot and mixed evenly to obtain a self-repairing prefabricated component crack repair material.

[0019] Beneficial effects of the present invention:

[0020] The present invention connects polyurethane to the side chain of the modified epoxy resin, so that on the one hand, a tightly entangled three-dimensional network structure can be constructed on the surface of the modified epoxy resin, thereby improving the toughness of the modified epoxy resin and thus enhancing the toughness of the crack repair material; on the other hand, during the curing process of the modified epoxy resin, the isocyanate group of the side chain can react with water to produce an unstable intermediate containing amino formic acid, which is then decomposed to produce carbon dioxide, so that the crack repair material produces micro-expansion, and the crack repair material is promoted to diffuse into the crack, so that the repair material can be better filled into fine cracks and interface gaps, effectively avoiding the curing shrinkage phenomenon of the epoxy resin, and giving the crack repair material excellent mechanical strength and interface bonding strength;

[0021] In addition, the crack repair material of the present invention contains self-repairing capsules. When cracks occur again, the self-repairing capsules rupture under the stress at the crack tip, and the capsule core diphenylmethane diisocyanate is released in time. The diphenylmethane diisocyanate can penetrate into the cracks and quickly react with the water or moisture in the cracks to bond and seal the cracks, thereby repairing the cracks that have occurred again, and giving the crack repair material good self-repairing properties.

[0022] The present invention introduces a modified epoxy resin with micro-expansion performance and a self-repairing capsule with good repair performance, thereby effectively avoiding secondary cracks caused by curing shrinkage of the crack repair material, enhancing the self-repairing performance of the repair material, and improving the crack repair efficiency. At the same time, silicate cement and fly ash are used as aggregates to enhance the density of the repair material and further enhance the strength of the repair material. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] This embodiment provides a modified epoxy resin, which is prepared by the following steps:

[0026] A1. Add 8.9 mL of 2,4-toluene diisocyanate to 16 mL of polyether diol, stir and mix, react for 1 h under nitrogen atmosphere at 60 °C, cool, add 8 mL of 1,4-butanediol and 12.7 g of trimethylolpropane, continue to react for 2 h at room temperature, and then obtain a prepolymer intermediate by rotary evaporation;

[0027] A2. Add 8 mL of the prepolymer intermediate to 20 mL of epoxy resin, stir and mix, then add 2 mL of trimethylolpropane triglycidyl ether, stir and react under a nitrogen atmosphere at 110° C. for 1 h, and cool to obtain a modified epoxy resin.

[0028] Example 2

[0029] This embodiment provides a modified epoxy resin, which is prepared by the following steps:

[0030] A1. Add 9.3 mL of 2,4-toluene diisocyanate to 17 mL of polyether diol, stir and mix, react for 1.5 h under nitrogen atmosphere and 70 ° C., cool, add 10 mL of 1,4-butanediol and 13.1 g of trimethylolpropane, continue to react for 3 h at room temperature, and then obtain a prepolymer intermediate after rotary evaporation;

[0031] A2. Add 10 mL of the prepolymer intermediate to 23 mL of epoxy resin, stir and mix, then add 4 mL of trimethylolpropane triglycidyl ether, stir and react under a nitrogen atmosphere at 115° C. for 1.5 h, and cool to obtain a modified epoxy resin.

[0032] Example 3

[0033] This embodiment provides a modified epoxy resin, which is prepared by the following steps:

[0034] A1. Add 9.6 mL of 2,4-toluene diisocyanate to 18 mL of polyether diol, stir and mix, react for 2 h under nitrogen atmosphere at 80 °C, cool, add 13 mL of 1,4-butanediol and 13.4 g of trimethylolpropane, continue to react for 4 h at room temperature, and then obtain a prepolymer intermediate by rotary evaporation;

[0035] A2. Add 13 mL of the prepolymer intermediate to 25 mL of epoxy resin, stir and mix, then add 6 mL of trimethylolpropane triglycidyl ether, stir and react for 2 h at 120° C. in a nitrogen atmosphere, and cool to obtain a modified epoxy resin.

[0036] Comparative Example 1

[0037] Compared with Example 3, the difference is that no prepolymer intermediate is added, and the epoxy resin is directly placed in the trimethylolpropane triglycidyl ether diluent, and the other raw materials and steps are the same.

[0038] Example 4

[0039] This embodiment provides a self-repairing capsule, which is prepared by the following steps:

[0040] 19 g of polyethylene wax was stirred and dissolved at 120 °C, and then 21 g of paraffin was added. After continuing to stir and dissolve, the temperature was kept constant, 76 mL of diphenylmethane diisocyanate was added, and stirred at a speed of 700 rpm for 2 hours. The temperature was then lowered to 100 °C, 400 mL of perfluorotributylamine was added, and stirring was continued for 20 minutes. The temperature was then quickly lowered to 15 °C and ultrasonically oscillated for 30 minutes. After filtering, washing, and drying, self-healing capsules were obtained.

[0041] Example 5

[0042] This embodiment provides a self-repairing capsule, which is prepared by the following steps:

[0043] Stir and dissolve 25g of polyethylene wax at 120°C, then add 25g of paraffin, continue stirring and dissolving, keep the temperature unchanged, add 79mL of diphenylmethane diisocyanate, stir at 750rpm for 2.5h, then cool to 105°C, add 400mL of perfluorotributylamine, continue stirring for 25min, then quickly cool to 18°C ​​and ultrasonically oscillate for 30min, and then filter, wash and dry to obtain self-healing capsules.

[0044] Example 6

[0045] This embodiment provides a self-repairing capsule, which is prepared by the following steps:

[0046] Stir and dissolve 31g of polyethylene wax at 120°C, then add 28g of paraffin, continue stirring and dissolving, keep the temperature unchanged, add 82mL of diphenylmethane diisocyanate, stir at 800rpm for 3h, then cool to 110°C, add 400mL of perfluorotributylamine, continue stirring for 30min, then quickly cool to 20°C and ultrasonically oscillate for 30min, and then filter, wash and dry to obtain self-healing capsules.

[0047] Comparative Example 2

[0048] Compared with Example 6, the difference is that the polyethylene wax is replaced by paraffin wax in equal amount, and the other raw materials and steps are the same.

[0049] Example 7

[0050] This embodiment provides a self-repairing prefabricated component crack repair material, which is prepared by the following steps:

[0051] 9 parts by weight of the modified epoxy resin prepared in Example 1, 0.5 parts by weight of a curing agent, 8 parts by weight of the self-repairing capsules prepared in Example 4, 90 parts by weight of Portland cement, 20 parts by weight of fly ash, and 3 parts by weight of a diluent are placed in a stirring pot and mixed evenly to obtain a self-repairing prefabricated component crack repair material.

[0052] Example 8

[0053] This embodiment provides a self-repairing prefabricated component crack repair material, which is prepared by the following steps:

[0054] 11 parts by weight of the modified epoxy resin prepared in Example 2, 1 part by weight of a curing agent, 9 parts by weight of the self-repairing capsules prepared in Example 5, 95 parts by weight of Portland cement, 25 parts by weight of fly ash, and 4 parts by weight of a diluent are placed in a stirring pot and mixed evenly to obtain a self-repairing prefabricated component crack repair material.

[0055] Example 9

[0056] This embodiment provides a self-repairing prefabricated component crack repair material, which is prepared by the following steps:

[0057] 13 parts by weight of the modified epoxy resin prepared in Example 3, 2 parts by weight of a curing agent, 10 parts by weight of the self-repairing capsule prepared in Example 6, 100 parts by weight of Portland cement, 30 parts by weight of fly ash, and 5 parts by weight of a diluent are placed in a stirring pot and mixed evenly to obtain a self-repairing prefabricated component crack repair material.

[0058] Comparative Example 3

[0059] Compared with Example 7, the difference is that the epoxy resin prepared in Comparative Example 1 is used, and the other raw materials and steps are the same.

[0060] Comparative Example 4

[0061] Compared with Example 7, the difference is that the self-repairing capsules prepared in Comparative Example 2 are used, and the other raw materials and steps are the same.

[0062] Comparative Example 5

[0063] Compared with Example 7, the difference is that the modified epoxy resin is replaced by an equal amount of commercially available toluene diisocyanate, and the other raw materials and steps are the same.

[0064] Performance tests were performed on Examples 7 to 9 and Comparative Examples 3 to 5. Compression and flexural properties: the repair material was made into a sample with a specification of 40 mm × 40 mm × 160 mm, and cured indoors at 20±2°C for 28 days. Referring to GB / T 17671-2021, compression and flexural strength tests were performed; bonding tensile strength: the repair material was made into a sample with a specification of 70 mm × 70 mm × 20 mm, and bonding tensile strength tests were performed according to DL / T 5126-2001. The results are shown in Table 1:

[0065] Table 1

[0066] project Example 7 Example 8 Example 9 Comparative Example 3 Comparative Example 4 Comparative Example 5 Compressive strength / MPa 74.8 76.2 83.4 60.3 68.3 64.8 Flexural strength / MPa 8.6 8.7 9.0 7.4 7.1 6.4 Bond tensile strength / MPa 4.8 5.1 5.6 3.8 4.4 4.1

[0067] It can be seen from Table 1 that the compressive strength and flexural strength of the crack repair agent prepared by modified epoxy resin and self-repairing capsules in Examples 7-9 are significantly higher than those in Comparative Examples 3-5, and have good mechanical strength. At the same time, the bonding tensile strength can reach up to 5.6 MPa, and has good bonding performance. In addition, compared with Comparative Examples 3 and 4, Example 7 has higher strength, indicating that the crack repair material prepared by the synergistic combination of modified epoxy resin and self-repairing capsules has better mechanical strength and bonding strength.

[0068] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0069] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A self-repairing prefabricated component crack repair material, characterized in that: It includes the following raw materials in parts by weight: 9-13 parts of modified epoxy resin, 0.5-2 parts of curing agent, 8-10 parts of self-repairing capsules, 90-100 parts of Portland cement, 20-30 parts of fly ash, 3-5 parts of diluent; The modified epoxy resin is prepared by the following steps: A1. Add 2,4-toluene diisocyanate to the polyether diol, stir and mix, react for 1-2 hours under a nitrogen atmosphere at 60-80° C., cool, then add 1,4-butanediol and trimethylolpropane, continue to react for 2-4 hours at room temperature, and then obtain a prepolymer intermediate by rotary evaporation; A2. Add the prepolymer intermediate to the epoxy resin, stir and mix, then add trimethylolpropane triglycidyl ether, stir and react for 1-2 hours under a nitrogen atmosphere at 110-120° C., and cool to obtain a modified epoxy resin.

2. A self-repairing prefabricated component crack repair material according to claim 1, characterized in that: The dosage ratio of the polyether diol, 2,4-toluene diisocyanate, 1,4-butanediol and trimethylolpropane is 16-18 mL: 8.9-9.6mL: 8-13mL: 12.7-13.4g.

3. The self-repairing prefabricated component crack repair material according to claim 1, characterized in that: The volume ratio of the epoxy resin, the prepolymer intermediate and trimethylolpropane triglycidyl ether is 20-25:8-13:2-6.

4. The self-repairing prefabricated component crack repair material according to claim 1, characterized in that: The self-repairing capsule is prepared by the following steps: The polyethylene wax is stirred and dissolved at 120°C, and then paraffin is added. After continuing to stir and dissolve, the temperature is kept constant, diphenylmethane diisocyanate is added, and stirring is carried out at a rotation speed of 700-800rpm for 2-3h, and then the temperature is reduced to 100-110°C, perfluorotributylamine is added, and stirring is continued for 20-30min, and then the temperature is quickly reduced to 15-20°C and ultrasonically oscillated for 30min, and then filtered, washed, and dried to obtain a self-healing capsule.

5. The self-repairing prefabricated component crack repair material according to claim 4, characterized in that: The dosage ratio of the polyethylene wax, paraffin, diphenylmethane diisocyanate and perfluorotributylamine is 19-31 g: 21-28 g: 76-82 mL: 400 mL.

6. The method for preparing a self-repairing prefabricated component crack repair material according to claim 1, characterized in that: The following steps are involved: The modified epoxy resin, curing agent, self-repairing capsule, silicate cement, fly ash and diluent are placed in a stirring pot and mixed evenly to obtain a self-repairing prefabricated component crack repair material.